2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malnutrition Is an Independent Predictor of Mortality, Length of Hospital Stay, and Hospitalization Costs in Stroke Patients

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 22 publications
2
129
2
8
Order By: Relevance
“…Several hypotheses have been proposed. First, a possible reason for the link between lower magnesium and in-hospital mortality is that lower magnesium at admission might reflect high BP [22,23], high blood glucose [24,25], severe state of malnutrition [26], and severe renal disease [27], which are known predictors of poor outcome and mortality of stroke in previous studies [28,29,30,31,32,33]. Second, previous animal studies indicated that magnesium could improve the blood flow in the ischemic area of the brain and enhance recovery of cellular energy metabolism after ischemia [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed. First, a possible reason for the link between lower magnesium and in-hospital mortality is that lower magnesium at admission might reflect high BP [22,23], high blood glucose [24,25], severe state of malnutrition [26], and severe renal disease [27], which are known predictors of poor outcome and mortality of stroke in previous studies [28,29,30,31,32,33]. Second, previous animal studies indicated that magnesium could improve the blood flow in the ischemic area of the brain and enhance recovery of cellular energy metabolism after ischemia [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The association between malnutrition and poor clinical outcomes has been established in previous medical studies [20] , and studies have shown that the median hospitalization time increases when patients are malnourished (NRS 2002 score ≥ 3) [21] . In our study, the total hospital LOS was significantly associated with hospital unit (p = 0.000), nutrition status (p = 0.000), and selfrated health (p = 0.000).…”
Section: Prolonged Hospital Staymentioning
confidence: 93%
“…In a recent study in two stroke units in south London, the use of a validated nutrition screening tool, i.e. the Malnutrition Universal Screening Tool (MUST), suggested around 30 % patients are at medium or high risk of malnutrition on admission to hospital following an acute stroke [ 26 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In a study of 537 patients screened using MUST within 72 h of hospital admission for acute stroke, there was a strong positive correlation between risk of malnutrition and mortality rate which remained signifi cant after adjustment for possible confounders [ 26 ]. At 6 months those patients who were at high risk of malnutrition on admission to hospital were twice as likely to die than those at low risk.…”
Section: Detectionmentioning
confidence: 99%